Technical pitfalls when collecting, cryopreserving, thawing, and stimulating human T-cells - Browne, Daniel J.; Miller, Catherine M.; Doolan, Denise L. (Frontiers in Immunology, 2024)
The collection, cryopreservation, thawing, and culture of peripheral blood mononuclear cells (PBMCs) can profoundly influence T cell viability and immunogenicity. Gold-standard PBMC processing protocols have been developed by the Office of HIV/AIDS Network Coordination (HANC); however, these protocols are not universally observed. Herein, we have explored the current literature assessing how technical variation during PBMC processing can influence cellular viability and T cell immunogenicity, noting inconsistent findings between many of these studies. Amid the mounting concerns over scientific replicability, there is growing acknowledgement that improved methodological rigour and transparent reporting is required to facilitate independent reproducibility. This review highlights that in human T cell studies, this entails adopting stringent standardised operating procedures (SOPs) for PBMC processing.We specifically propose the use of HANC's Cross-Network PBMC Processing SOP, when collecting and cryopreserving PBMCs, and the HANC member network International Maternal Pediatric Adolescent AIDS Clinical Trials (IMPAACT) PBMC Thawing SOP when thawing PBMCs. These stringent and detailed protocols include comprehensive reporting procedures to document unavoidable technical variations, such as delayed processing times.Additionally, we make further standardisation and reporting recommendations to minimise and document variability during this critical experimental period. This review provides a detailed overview of the challenges inherent to a procedure often considered routine, highlighting the importance of carefully considering each aspect of SOPs for PBMC collection, cryopreservation, thawing, and culture to ensure accurate interpretation and comparison between studies.